The effect of kinesio tape on post-injury performance among young athletes with chronic ankle injury - Haikal, Ekmal; Adnan, Aizzat; Linoby, Adam; Sazali, Razif; Zulqarnain, Muhammad; Md Yusoff, Yusandra; Abidin, Muhammad Amrun Haziq (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study evaluates the immediate effects of kinesio tape on range of motion, balance, and stability among thirty-four male athletes aged 7–18 suffering from chronic ankle instability. By comparing pre- and post-test results across control and experimental groups using measures such as the star excursion and side hop tests, the research aims to clarify the rehabilitative value of taping in post-injury performance. The findings seek to determine whether kinesio tape serves as an effective intervention for improving functional stability and reducing the risk of re-injury in young athletic populations.